Eksplorasi Pengalaman Pasien Spinal Cord Injury dalam Melakukan Adaptasi Rumah Pascaperawatan di RSUP Dr. Sardjito: Studi Kualitatif - Najhan, Muhammad Azka; Triyanto, Arifin; Mulyani, Sri (PSIK FKKMK UGM, 2026)
Background: Spinal cord injury (SCI) is a condition that causes physical, psychological, and social impairments and is a leading cause of disability. After hospital discharge, patients face challenges in adapting to the home environment, which may affect their independence and quality of life. Studies exploring the subjective experiences of patients with spinal cord injury in adapting to home environments after discharge in Indonesia remain limited. Objective: This study aimed to explore the experiences of patients with spinal cord injury in adapting to home environments after discharge from RSUP Dr. Sardjito. Methods: A qualitative study with a descriptive exploratory approach was conducted involving eight patients with spinal cord injury who had been treated at RSUP Dr. Sardjito between January 2024 and October 2025. Participants were selected using purposive sampling based on inclusion and exclusion criteria. Data were collected through semi-structured interviews. Data analysis followed the stages proposed by Erlingsson and Brysiewicz. Results: The analysis identified four main themes: (1) limitations in physical adaptation; (2) psychological conditions, including emotional responses, expectations, and coping strategies; (3) the adaptation environment, reflecting spatial adjustments, the use of assistive devices, rehabilitation processes, as well as family and social support; and (4) determinants of adaptation, including home-related barriers and economic conditions influencing the ability to adapt. Conclusion: Patients with spinal cord injury experience a complex process of home adaptation involving physical, psychological, social, and environmental aspects.INTISARILatar belakang: Spinal cord injury (SCI) merupakan cedera yang menimbulkan gangguan fisik, psikologis, dan sosial serta menjadi penyebab utama kecacatan. Setelah keluar dari rumah sakit, pasien menghadapi tantangan dalam beradaptasi di rumah yang dapat memengaruhi kemandirian dan kualitas hidup. Penelitian yang mengeksplorasi pengalaman subjektif pasien spinal cord injury dalam melakukan adaptasi rumah pascaperawatan di Indonesia masih terbatas. Tujuan: Penelitian ini bertujuan untuk mengeksplorasi pengalaman pasien spinal cord injury dalam melakukan adaptasi rumah pascaperawatan di RSUP Dr. Sardjito Metode: Penelitian kualitatif dengan pendekatan deskriptif eksploratif melibatkan delapan pasien spinal cord injury yang pernah dirawat di RSUP Dr. Sardjito pada Januari 2024-Oktober 2025. Partisipan dipilih menggunakan teknik purposive sampling berdasarkan kriteria inklusi dan eksklusi. Pengumpulan data dilakukan melalui wawancara semi terstruktur. Analisis data mengikuti tahapan Erlingsson dan Brysiewicz. Hasil: Analisis data menghasilkan empat tema utama, yaitu: (1) keterbatasan adaptasi fisik; (2) situasi psikologis yang meliputi respons emosional, harapan, dan strategi koping; (3) suasana adaptasi yang mencerminkan penyesuaian ruang, penggunaan alat bantu, proses rehabilitasi, serta dukungan keluarga dan sosial; dan (4) penentu adaptasi yang mencakup hambatan di rumah serta kondisi ekonomi yang memengaruhi kemampuan adaptasi. Simpulan: Pasien spinal cord injury mengalami proses adaptasi rumah yang kompleks yang melibatkan aspek fisik, psikologis, sosial, dan lingkungan.